The Influence Of Blended Learning Method On Learning Outcomes In English Subject At Sekolah Indonesia Kuala Lumpur (Sikl)Malaysia - Irma Nurhana; Hastri Firharmawan; Eka Nurhidayat (English Language Education Department, Universitas Majalengka, 2024)
Blended Learning has become one of the most commonly used ways of classroom learning, one of which is used in English language learning due to its dual component, which integrates Face-to-Face classes with virtual learning to offer students a variety of methodologically organized materials and resources. In this era of digitalization, teachers and students have changed the way the educational process is viewed as new technologies have been implemented and teachers have to propose new ways of working to display materials that complement English learning in the classroom. The purpose of this research is to obtain clear information about the effect of blended learning model to improve students' learning outcomes and its role in the learning process, especially in English subjects. From the results of the study, it can be seen that the average value of learning outcomes in the experimental class has increased significantly, where the average value of posttest learning 71.8 is greater than the value of pretest learning 52.67, so that the blended learning model affects student learning outcomes more than the conventional model. In this study, it is clear that the blended learning model is able to provide changes in student learning outcomes, so that the blended learning model becomes one of the learning models that can be used to improve student learning outcomes.